Ulos Fabric Dyeing Process as Ethnoscience-Based Science Learning Resource - Pratama, Danang Habib; L, Laily Rochmawati; Sujatmika, Sigit (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This study aimed to identify the science concepts in the dyeing process of Ulos woven fabrics that will be used as a science learning resource for junior high schools. An ethnoscience study by exploring the original science contained in a community group based on scientific science. This study used a qualitative method with an ethnographic approach through the process of data reduction, data presentation, conclusion drawing, and verification. The location of research was carried out at the Ulos Batak By Gallery at Manjunjung Hutabarat, Jl. Major General. Y Samosir No, 76, Partalijulu Village, Tarutung District, North Tapanuli Regency, North Sumatra, Indonesia. The instruments used were observation sheets, interview guidelines, and questionnaires. Collecting data through participatory observation, in-depth interviews, documentation, and questionnaires. To test the validity of the data using triangulation techniques (source, technique, and time). Based on the results of the study, it is known that the natural dyeing process in the manufacture of Ulos fabric includes the preparation of materials (plants), the plant processing stage, the dissolving stage of natural dyes, the dyeing stage, the drying stage, the fixation stage, the washing stage, and the final drying stage. The science concepts in the curriculum 2013 are in accordance with the process of coloring Ulos cloth, and namely plant classification, solid pressure, heat transfer, physical changes, energy in living systems, separation of mixtures, boiling points, temperatures and their changes, chemical changes, elements, compounds, mixtures. It can be concluded that the manufacture of Ulos woven fabric in this study is a learning resource that can integrate learning materials in various fields of science fabrics (physics, biology).